PENGARUH GREEN MARKETING, PERSEPSI HARGA, DAN KUALITAS LINGKUNGAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PROPERTI BERKONSEP ECO-FRIENDLY DI KOTA MAKASSAR - Saadiah; Muhammad Idris; Samsul Alam; Maryadi; Yuswari Nur (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the influence of green marketing, price perception, and environmental quality on consumer purchasing decisions for environmentally friendly properties in Makassar City. Using a quantitative approach, data was collected through questionnaires distributed to 120 respondents who had shown interest in or had previously purchased environmentally friendly properties. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) techniques. The results of the study indicate that green marketing has a significant positive influence on consumer purchasing decisions. Price perception also plays an important role in shaping consumers' desire to purchase, particularly in relation to value for money and price transparency. Additionally, environmental quality—such as the availability of green open spaces, clean air, and sustainable design—has a significant influence on purchasing decisions. This study provides practical implications for property developers and marketers to strengthen their positioning in the environmentally friendly property segment by emphasizing environmentally conscious marketing strategies, competitive pricing, and superior environmental quality. This study also contributes to academic discourse by enriching empirical evidence on sustainable consumer behavior in the property sector.